O Eusébio de Constantino e o Constantino de Eusébio: o início das relações de poder entre a Igreja e o Estado - Ramalho, Jefferson (2012)
This research aims to investigate the history of christian religion historiography throughout an analyses of the work Ecclesiastical History of Eusebius of Caesarea from the early fourth century of our era. In this sense, the proposals presented by the AnnalesSchool, especially the History-Problem, are used as a theoretical reference for the development of the criticism. At first, it is observed the characteristics of Eusebius the writer and the politician,which the emperor Constantine was concerned. Finally, the specific character observed along the work to exemplify its apologetic and panegyrist style is the heroic image of the emperor Constantine that Eusebius developed. In order to verify this development, the parameters of Annales History-Problem are usedand also the concept of Invention of Traditions. Once identified that Constantine had the help of a christian writer, bishop and ecclesiastical-political that corresponded to his interests, and Eusebius that simultaneously built an benevolent image of the emperor, it is possible in this thesis to see how the Eusebian narrative and discourse accomplishes both political and religious motivations that can not be disregarded. This verification becomes even more important when we note how the Eusebian model of writing history served as a reference for so many others who had taken place laterin the same enterprise